Experimental-numerical method of selecting the model of moisture emission from the surface of water in a swimming pool basin - Ciuman, Piotr (Instal, 2021)
The issue of indoor swimming pool ventilation is very complex, which is a serious problem in their proper design and modernization. The difficulty is that in Poland there are no uniform regulations and standards regarding the required values of ventilation air parameters, the method of calculating moisture emission and the value of the venti lation air volume flow rate. In research, design and modernization of ventilation systems for swimming pools, vari ous methods are used to determine the emission of moisture from the water in the swimming pool basin and there is no complete information as to which of them best reflects the actual thermal-moisture and airflow phenomena. This paper presents a developed and validated research method related to the modeling of moisture emission from the pool water surface, which can be used for the modernization of ventilation systems in the existing indoor swimming pools, due to the need to improve thermal-moisture conditions.